Pengujian Kualitas Air Sumur Km.10 Kota Sorong Berdasarkan Parameter Fisika dan Kimia - Azalia Fajri Yasin; Azwar Rahmatullah; Aldi Suma (Pelantar Press, 2024)
Most residents in Kilo 10, Sorong City, use well water for daily needs. One common issue is the presence of iron in the well water, which causes rust and brown stains on clothes or household items. This study aims to determine the pH, TDS (Total Dissolved Solids), salinity, conductivity, turbidity, TSS (Total Suspended Solids), and temperature in well water. The well water samples were taken from areas with neutral pH (Sumbersari), basic pH (Puger), and acidic pH (Kencong). The results showed that the pH of the well water samples was 6.2, TDS was 185, indicating that the well water met the standards. The salinity was 150 or 1.5 mg/L, and the conductivity of pure water ranged from 0-200 Î¼S/cm (low conductivity), large river water ranged from 200-1000 Î¼S/cm (mid-range conductivity), and saline water was 1000-10000 Î¼S/cm (high conductivity). The conductivity value for potable water is around 42-500 Î¼S/cm. The turbidity result was 19 NTU, indicating that the well water sample was not suitable for drinking. The TDS value was high at 667, and the temperature was 30.5Â°C.